Comparing reactogenicity of COVID-19 vaccine boosters: a systematic review and meta-analysis - Alberto San Francisco Ramos; Carolina Liu Sanchez; Tatiana Bovill Rose; David Smith; Natasha Thorn; Eva Galiza; Thahmena Miah; Jennifer Pearce; Cecilia Hultin; Catherine Cosgrove; Yingfen Hsia; Paul T. Heath (Taylor & Francis Group, 2024)
ABSTRACTIntroduction Different COVID-19 vaccines are being utilized as boosters. This systematic review and meta-analysis aims to evaluate the reactogenicity of COVID-19 vaccines given as booster doses, according to vaccine type, dose, timing, participant characteristics and primary immunization regimen received.Methods Four databases (MEDLINE, Embase, Web of Science and CENTRAL) were searched for randomized controlled trials between 1 January 2020 and 1 January 2023 according to predetermined criteria.Results Twenty-eight studies describing 19 vaccines of four different types (viral vector, inactivated, mRNA and protein sub-unit) were identified. BNT162b2 vaccine (Pfizer-BioNTech) was selected as the control as it was most often compared with other vaccines. Fever, fatigue, headache, injection-site pain, redness, and swelling were the most frequently reported solicited events. mRNA vaccines were the most reactogenic, followed by viral vector vaccines and protein sub-unit vaccines, while inactivated vaccines were the least reactogenic. Full-dose vaccines were more reactogenic than half-dose vaccines. Heterologous BNT162b2 boosters were more reactogenic than boosters with the same vaccine used for primary immunization.Conclusions COVID-19 vaccine booster schedules have distinct reactogenicity profiles, dependent on dose and vaccine type, which may allow targeted recommendations and provide choice for specific populations. Greater standardization of adverse event reporting will aid future studies.